Digital-Based Curriculum Development in Improving Students' Religious Literacy - Indah Riwayati; Eti Mayasari; Nurul Mubin (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
The massive advancement of digital technology demands a reconstruction of the Islamic Religious Education (PAI) curriculum to remain relevant to the characteristics of the digital native generation and strengthen students' religious literacy in the era of information disruption. This study aims to formulate the concept of digital-based curriculum development and analyze the effectiveness of integrating Interactive Flat Panel (IFP) technology in enhancing students' religious literacy. The method employed is library research with a descriptive qualitative approach. Data sources are classified into primary data, consisting of fundamental curriculum theory literature, and secondary data, comprising accredited scientific journal articles and related policy documents. The data collection technique utilizes digital documentation studies through Google Scholar and Sinta databases, while the data analysis technique applies content analysis through reduction, categorization, interpretation, and drawing conclusions. The results indicate that: (1) The characteristics of the PAI digital curriculum systematically integrate goals, multimedia materials, and interactive strategies while maintaining moral-spiritual values as the ultimate achievement; (2) IFP integration transforms conventional classroom climates into participatory, multimedia, and contextual learning ecosystems; (3) This IFP-based curriculum is proven to holistically boost students' religious literacy while serving as a preventive instrument against online radicalism narratives by providing access to authoritative digital sources; (4) The implementation of this curriculum still faces challenges, such as infrastructure limitations and teachers' digital competence, thereby requiring adaptive curriculum models and sustainable technology training.